2016
DOI: 10.1002/cphc.201500868
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Inner‐Shell Architecture on Quantum Yield and Blinking Dynamics in Core/Multishell Quantum Dots

Abstract: Choosing the composition of the shell for QDs is not trivial, since both the band-edge energy offset and interfacial lattice mismatch play roles in influencing the final optical properties. One way to balance these competing effects is by forming multi-shells and/or gradient-alloyed shells. However, this introduces multiple interfaces and their relative effects on quantum yield and blinking are not yet fully understood. Here we undertake a systematic, comparative study of adding inner shells of single composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…However, the correlation of the amplitude of this fast component with on-state intensity and its anticorrelation with average on dwell time, at least for QDs with 5 ML of CdS shell, seems to be in contradiction with this assignment. It is worth noting at this point that the relative amplitudes of the fluorescence lifetime components in the ensemble and single molecule experiments did not agree with each other, similar to our previous reports, which may be due to a dark fraction not observable in single QD measurements. , We had also previously postulated the existence of slow-blinking and fast-blinking events in core/multishell QDs …”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, the correlation of the amplitude of this fast component with on-state intensity and its anticorrelation with average on dwell time, at least for QDs with 5 ML of CdS shell, seems to be in contradiction with this assignment. It is worth noting at this point that the relative amplitudes of the fluorescence lifetime components in the ensemble and single molecule experiments did not agree with each other, similar to our previous reports, which may be due to a dark fraction not observable in single QD measurements. , We had also previously postulated the existence of slow-blinking and fast-blinking events in core/multishell QDs …”
Section: Discussionsupporting
confidence: 57%
“…CdSe core samples were synthesized by modification of the literature methods. , Briefly, 0.04 M cadmium (Cd) precursor was prepared by degassing under vacuum and then heating a mixture of 0.02565 g of CdO, 0.4452 g of OA, and 2 g of ODE to 200 °C under argon flow until the solution became clear. The temperature was then reduced to 50 °C, and then 1.5092 g of ODA and 0.5026 g of TOPO wre added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1(c), when compared with traditional II-VI QDs. For example, the absorption and emission spectra of monodisperse hydrophobic thick shell CdSe/CdS QD in hexane with a QY close to 1 show a FWHM of the first sharp excitonic absorption maximum of about 37 meV and a FWHM of the emission band of 65 meV [64][65][66][67]. The spectral widths of the emission bands were obtained assuming a symmetric shape of the emission spectra that were only recorded up to 790 nm.…”
Section: Time and Temperature Optimizationmentioning
confidence: 99%
“…At e m t on / ). 23,28,30,55−57 More recent studies have questioned the power law model and instead proposed that a multiexponential model is more suitable, 31,58 particularly as far as the on dwell times are concerned ( = ∑ τ − P A e i i t on / i ). Our group recently compared the reduced χ 2 values when fitting CdSe-based core/shell QDs to both models and found that on dwell times do fit better to a multiexponential model than an inverse power law although it was not possible to distinguish between the models for the off dwell times.…”
mentioning
confidence: 99%